“Floral Ornament of Reality”: Flowers in Worldview of E. T. A. Hoffmann and N. A. Polevoy - N. M. Ilchenko; E. G. Chernysheva (Научный диалог, 2024)
The relevance of this study is grounded in the scholarly significance of the issue of Russian-German literary connections as a crucial factor in intercultural interaction. This article analyzes works in which the authors articulate a mystical sense of nature, based on the natural philosophical ideas of F. Schelling. The focus of the investigation is the national distinctiveness of Romanticism, manifested in the peculiarities of nature perception, particularly floral imagery. It is demonstrated that the Romantic writers of Germany and Russia perceived love, within the value-emotional framework of the Romantic universe, as a mystical feeling that enables one to penetrate the mysterious forces of nature. The floral motifs within the works contribute an additional allegorical meaning to the artistic worlds of E. T. A. Hoffmann and N. A. Polevoy. The “floral background” of the characters in the analyzed texts (the tulip Gamachea, the thistle Pepush, the bride Tis — Little Rose; Emma — cornflower; Italy — “poor forget-me-not,” among others) establishes a symbolic language of nature. Attention is also given to motifs traditional to German literature: yearning, soul affinity, reminiscence of a “different world,” and the union of lovers in death, which are reflected in the examined works of Russian literature. The novelty of this research lies in its consideration of N. A. Polevoy’s dialogue with the German literary tradition represented by E. T. A. Hoffmann as a result of his philosophical and poetic explorations.